The impact of entrepreneur education on business performance / Rosman Mahmood ... [et al.] - Mahmood, Rosman; Mohd Zahari, Ahmad Suffian; Ibrahim, Norlaila; Nik Jaafar, Nik Fazlin Hiryati; Yaacob, Najihah Marha (Universiti Teknologi MARA, 2020)
The importance of entrepreneurial role in supporting the country's economic growth has been recognized by experts in the field of entrepreneurship. Today the importance of entrepreneurship has become increasingly important where it has turned into a priority for developing countries including Malaysia. Now, there are many higher educational institutions that are aware of the importance of applying entrepreneurial skills in higher education. Therefore, public universities have to implement entrepreneurship education to encourage students to venture into entrepreneurship. This study examined the effects of entrepreneurship education in influencing business performance among ITM/UiTM graduates. A total of 250 graduates from various businesses in Malaysia participated voluntarily in this study by completing survey questionnaires. A series of statistical analysis were applied including descriptive analysis, reliability analysis, correlation analysis, and multiple regressions analysis using the SPSS software. The results of the study indicate that university curriculum, relational factor, society factor, and entrepreneurship values were found to have significant influences on business performance. However, the results revealed that the university role has no significant influence on business performance. The findings of this study contribute to entrepreneurship education and entrepreneurship literature by adding new empirical evidence on the relationship between university curriculum, relational factors, society factor, and entrepreneurship values on business performance. In terms of managerial implications, the findings help HEI’s in organizing entrepreneurship education dimensions, particularly in strategizing, marketing, decision making, and positioning themselves in the business industry.